Stress psychosocial de l’enfant et excrétion urinaire de cortisol : impact du type de structure familiale et de l’expérience de migration - Hélène Pagezy; Valérie Niel-Bernard; Pierre Darlu (Bulletins et Mémoires de la Société d’Anthropologie de Paris)
The relationship between migration, family structure and stress level was investigated in an anthropological study carried out in Marseilles on 60 children of Senegalese origin, 5 to 15 years old. The biological stress level was assessed through the 24h cortisol level in urine samples, standardized according to sex and age. These children lived either in nuclear families or in family structures of another type. Some children had recently experienced migration whereas others were born or had lived in France for more than 3 years. It appears that the children living in non-nuclear families, having recently migrated and encountering difficulties at school or in integration, show significantly higher cortisol levels, suggesting that they experience higher levels of stress.